Peningkatan Literasi Analisa Laporan Keuangan: Analisis Pemberian Pinjaman - Nuha, Sukma Uli; Reviandani, Wasti; Vilantika, Elok (Jurnal Pengabdian Manajemen, 2024)
Community Service was held for students of the Faculty of Economics and Business, Universitas Muhammadiyah Gresik who taught the Financial Report Analysis course entitled "Improving Financial Report Analysis Literacy: Loan Analysis". This activity aims to improve students' understanding and ability in analyzing financial reports regarding loan / credit analysis. This community service activity was carried out at the Sang Pencerah Hall, Universitas Muhammadiyah Gresik which is located at Jl. Sumatera No. 101, Gn. Malang, Randuagung, Kec. Kebomas, Kab. Gresik, East Java. This community service activity was carried out on June 27, 2024. This activity was attended by approximately 100 students by presenting expert speakers in the field of finance who were also members of the FEB UMG Community Service Team. The material presented included the concept of preparing financial reports, the basic nature of financial reports, the purpose of preparing financial reports, financial report analysis, credit / loan analysis and calculation of credit / loan analysis. Participants showed enthusiasm and positive responses and felt that this material was very relevant and useful to support student knowledges